2000
DOI: 10.1034/j.1600-0404.2000.102003162.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in beta-thalassemia major

Abstract: Our findings suggest that beta-th is associated with neuropsychological impairment involving multiple cognitive domains and argue for a potential role of hemosiderosis on cognitive functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 0 publications
7
71
3
5
Order By: Relevance
“…Our findings support the results of other studies [2][3][4][5][6][7][8][9][10][11][12][13][14] on the quality of life of TM patients and those with other chronic diseases, including Crohn disease, ulcerative colitis, cystic fibrosis, congenital heart disease, asthma, epilepsy, sweet diabetes and cancer [23--26]. These studies found that patients with these diseases show a significant decrease in life satisfaction and mental health or a significant increase in probable psychiatric disorders, including somatisation, interpersonal sensitivity, depression, anxiety and psychosis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings support the results of other studies [2][3][4][5][6][7][8][9][10][11][12][13][14] on the quality of life of TM patients and those with other chronic diseases, including Crohn disease, ulcerative colitis, cystic fibrosis, congenital heart disease, asthma, epilepsy, sweet diabetes and cancer [23--26]. These studies found that patients with these diseases show a significant decrease in life satisfaction and mental health or a significant increase in probable psychiatric disorders, including somatisation, interpersonal sensitivity, depression, anxiety and psychosis.…”
Section: Discussionsupporting
confidence: 83%
“…These treatments can also have an impact on the families of patients, especially on siblings [2][3][4][5][6][7][8][9][10]. Some investigations have found that 80% of people diagnosed with TM have at least 1 psychiatric disorder [2], the most frequent being disembodiment [3,4], anxiety [5,6], depression [7], somatoform disorders [8] and anger [9,10]. This disease can also have a deleterious impact on the social activities and education of patients [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on 46 patients with b-thalassemia major, it was reported that the neuropsychological tests were significantly impaired especially in patients with signs of hemosiderosis [26]. In this study, a significant relationship was shown between the timing of institution and duration of transfusion and chelation therapies and neurological findings, while there was no correlation between desferrioxamine doses, hemoglobin, and ferritin levels.…”
Section: Discussionmentioning
confidence: 47%
“…In addition, factors associated with chronic illness leading to regular school absence, physical and social restrictions, abnormal mental state, rather than the disease per se, could also play a potential role in the development of cognitive dysfunction in patients with thalassemia. 2,3 It would have been interesting to evaluate the effect of the various chelation agents on iron deposition. Although our preliminary results showed no significant differences, this retrospective study was limited by the confounding variable of different treatment times and the small sample size.…”
Section: Discussionmentioning
confidence: 99%